Tailoring Thermo‐Mechanical Properties of Cationically UV‐Cured Systems by a Rational Design of Vinyl Ether Ester Oligomers using Enzyme Catalysis. Issue 21 (4th October 2018) - Brännström, Sara; Finnveden, Maja; Razza, Nicolò; Martinelle, Mats; Malmström, Eva; Sangermano, Marco; Johansson, Mats
Abstract: There is a demand for new sustainable polymeric materials. Vinyl ethers are, in this context, attractive oligomers since they polymerize fast, are non‐toxic, and can be polymerized under ambient conditions. The availability of vinyl ether oligomers is, however, currently limited due to difficulties in synthesizing them without using tedious synthesis routes. This work presents the synthesis of a series of vinyl ether ester oligomers using enzyme catalysis under solvent‐free conditions and the subsequent photoinduced cationic polymerization to form polymer thermosets with T g s ranging from −10 to 100 °C. The whole process is very efficient as the synthesis takes less than 1 h with no need for purification and the crosslinking is complete within 2 min. Abstract : This work presents an efficient and benign enzymatic synthesis of vinyl ether ester oligomers for solvent‐free resin applications . The synthesis is complete in less than 1 h and the oligomers are thereafter crosslinked during 2 min with UV‐initiated cationic polymerization, which yielded transparent free‐standing films that have a wide range of T g s from −10 to 100 °C depending on composition.